Peran Orang Tua Dalam Memotivasi Anak Untuk Melanjutkan Studi Ke Perguruan Tinggi (Studi di Desa Takal Pasir, Kecamatan Singkil, Kabupaten Aceh Singkil) - sri, sri mulyani; Rusnawati (Program Studi Kesejahteraan Sosial Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Ar-Raniry, 2024)
The role of parents who pay less attention to their children's education can be caused by the low level of education obtained by parents during their education and a lack of understanding of the Role of Parents in Motivating Children to Continue Their Studies to College, the importance of education for life. Seeing the development of this increasingly advanced era, all aspects of life really need education. The purpose of this study is to determine the role of parents in motivating children to continue their studies to college in Takal Pasir Village, Singkil District, Aceh Singkil Regency, to describe the supporting and inhibiting factors of parents in motivating children to continue their studies to college in Takal Pasir Village, Singkil District, Aceh Singkil Regency. This study uses a qualitative approach, with a type of field research. The informants in this study were parents of children who continued their education to college or who did not continue their education to college as many as 9 informants. The data collection techniques used in this study were interviews, observation and documentation. The data analysis method used in this study was the qualitative field analysis method. The results of this study indicate that the role of parents in motivating children to continue their studies to college in Takal Pasir Village can be seen from the enthusiasm of parents in seeking information about college. Parents also provide psychological encouragement or intrinsic motivation to children such as giving advice on the importance of education. Then parents facilitate children to college, so that children in Takal Pasir Village can be motivated to continue to college. There are supporting and inhibiting factors in motivating children to continue to college in Takal Pasir Village. Supporting factors such as the child's willingness, strong motivation from parents, enthusiasm from the child and a good economy. While the inhibiting factors for children not continuing to college such as intrinsic motivation in the child that does not exist, excessive laziness in children, no ideals and poor economy and environmental influences